Analysis Of Financial Statements To Measure Financial Performance In Go Public Companies On Idx (PT Ace Hardware Indonesia) - Dhea Agusty Ningrum (Jurnal Mantik, 2022)
In the financial statements, the possibility that occurs is getting a profit (profit) and getting a loss. The company earns a profit if the income or income is greater than the expenses. The company suffers a loss if the income is less than the expenses. The financial performance of the company cannot be said to be good if it is only seen from the profits that continue to increase. Financial performance assessment is carried out through financial statement analysis. Financial statement analysis used is liquidity ratio (current ratio, quick ratio, cash ratio), solvency ratio (debt to asset ratio, debt to equity ratio), profitability ratio (net profit margin, return on equity, return on investment) activity ratio (fixed asset turn over, total asset turn over). Not only through financial ratio analysis, however, financial performance assessment can be done by using Economic Value Added (EVA) analysis. At the company PT Ace Hardware Indonesia, Tbk, the company's financial performance in 2014 - 2017 based on the results of financial ratio analysis, can be said to be good. According to the results of the solvency ratio, the financial performance of the company PT Ace Hardware Indonesia, Tbk is not good. From the profitability ratio results, the financial performance of PT Ace Hardware Indonesia, Tbk is not good. Meanwhile, from the activity ratio of fixed asset turnover, the financial performance of PT Ace Hardware Indonesia, Tbk is quite good. However, from the activity ratio in terms of total asset turnover, the company's financial performance is not good. However, if viewed from the Economic Value Added (EVA), the financial performance of the company PT Ace Hardawre Indonesia is very good